2016
DOI: 10.1016/j.jaac.2015.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Mode of Anisotropy Reveals Global Diffusion Alterations in Attention-Deficit/Hyperactivity Disorder

Abstract: Objective Diffusion tensor imaging (DTI) can identify structural connectivity alterations in attention-deficit/hyperactivity disorder (ADHD). Most ADHD DTI studies have concentrated on regional differences in fractional anisotropy (FA) despite its limited sensitivity to complex white matter architecture and increasing evidence of global brain differences in ADHD. Here, we examine multiple DTI metrics in separate samples of children and adults with and without ADHD with a principal focus on global between-group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
19
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 43 publications
(58 reference statements)
5
19
0
3
Order By: Relevance
“…An earlier metaanalysis suggests that adults with ADHD have less extensive regions of brain structural abnormality than ADHD children [Frodl and Skokauskas, 2012]. A recent DTI study also reported the lack of significant regional WM differences, in terms of the FA values, in both children and adults with ADHD [Yoncheva et al, 2016], supporting the present negative results. Other explanations of this negative finding may involve sex/gender impacts [Villemonteix et al, 2015], in-scanner head motion [Koldewyn et al, 2014], sample size, and medication effects [Lin et al, 2014a].…”
Section: Figuresupporting
confidence: 79%
See 1 more Smart Citation
“…An earlier metaanalysis suggests that adults with ADHD have less extensive regions of brain structural abnormality than ADHD children [Frodl and Skokauskas, 2012]. A recent DTI study also reported the lack of significant regional WM differences, in terms of the FA values, in both children and adults with ADHD [Yoncheva et al, 2016], supporting the present negative results. Other explanations of this negative finding may involve sex/gender impacts [Villemonteix et al, 2015], in-scanner head motion [Koldewyn et al, 2014], sample size, and medication effects [Lin et al, 2014a].…”
Section: Figuresupporting
confidence: 79%
“…However, much less investigation has been conducted on adults with ADHD, compared to child population [Onnink et al, 2015]. A recent DTI study also reported the lack of significant regional WM differences, in terms of the FA values, in both children and adults with ADHD [Yoncheva et al, 2016], supporting the present negative results. A recent DTI study also reported the lack of significant regional WM differences, in terms of the FA values, in both children and adults with ADHD [Yoncheva et al, 2016], supporting the present negative results.…”
Section: Discussionsupporting
confidence: 67%
“…We attempted to contact all authors of TBSS studies; we received responses from 11 authors corresponding to 12 TBSS studies. Six authors responded that they could not assure a lack of group differences in head motion, while authors of five studies corresponding to six datasets assured the groups did not differ significantly in head motion (Adisetiyo et al., ; Cooper et al., ; Nagel et al., ; Van Ewijk et al., ; Yoncheva et al., ). Notably, only two of these datasets (Nagel et al., ; Van Ewijk et al., ) found any significant between‐group differences.…”
Section: Resultsmentioning
confidence: 99%
“…Details of included studies are provided in Table 1. Twelve studies with 13 datasets, including a total of 557 individuals with ADHD and 568 TD participants, were included in the meta-analysis of TBSS studies (Adisetiyo et al, 2014;Chuang, Wu, Huang, Weng, & Yang, 2013;Cooper, Thapar, & Jones, 2015;Cortese et al, 2013;De Luis-Garcia et al, 2015;King, Yurgelun-Todd, Stoeckel, Dimuzio, & Lopez-Larson, 2015;Nagel et al, 2011;O'conaill et al, 2015;Onnink et al, 2015;Silk, Vance, Rinehart, Bradshaw, & Cunnington, 2009;Van Ewijk et al, 2014;Yoncheva et al, 2016). Since one of two datasets in Cortese et al, recruited individuals with a current ADHD diagnosis, the study was included in the analysis (Cortese et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Encouragingly, the results from those studies overlap with ours in finding widespread regions, including decreased FA with or without increased RD in overlapping regions. In contrast, other studies failed to identify any regional alteration, in either children or adults with ADHD compared with healthy controls, even with comparable sample sizes (Ercan et al, 2016;Yoncheva et al, 2016). Inconsistency might result from differences in scanning, data processing, and quality assurance protocols, differences in demographic characteristics of the participants, eg, age (Roalf et al, 2016), sex (Jacobson et al, 2015), medication history (de Luis-Garcia et al, 2015), as well as the heterogeneous nature of the disorder (Thapar and Cooper, 2015).…”
Section: Discussionmentioning
confidence: 97%